2021
DOI: 10.1021/acs.nanolett.1c01792
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Nanocluster-Mediated Delivery of siRNA to Intact Plant Cells for Efficient Gene Knockdown

Abstract: RNA interference, which involves the delivery of small interfering RNA (siRNA), has been used to validate target genes, to understand and control cellular metabolic pathways, and to use as a "green" alternative to confer pest tolerance in crops. Conventional siRNA delivery methods such as viruses and Agrobacterium-mediated delivery exhibit plant species range limitations and uncontrolled DNA integration into the plant genome. Here, we synthesize polyethylenimine-functionalized gold nanoclusters (PEI-AuNCs) to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 35 publications
1
54
1
Order By: Relevance
“…While nanoparticle-mediated RNA delivery has been extensively explored in biological detection, disease therapy and pest control, its great potential application in plant systems is still needed exploration [ 11 15 ]. Previous studies have successfully applied nanoparticles to deliver plasmid DNA [ 16 18 ], dsRNA [ 19 ] or siRNA [ 20 22 ] to intact plant cells, showing that the nanoparticles can reach the plant tissues, cells and subcellular locations that are previously inaccessible. These representative nanoparticles include dendrimer [ 19 ], clay nanosheet [ 20 ], carbon nanotube [ 18 , 21 ], gold nanoclusters [ 22 ], carbon dot [ 23 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…While nanoparticle-mediated RNA delivery has been extensively explored in biological detection, disease therapy and pest control, its great potential application in plant systems is still needed exploration [ 11 15 ]. Previous studies have successfully applied nanoparticles to deliver plasmid DNA [ 16 18 ], dsRNA [ 19 ] or siRNA [ 20 22 ] to intact plant cells, showing that the nanoparticles can reach the plant tissues, cells and subcellular locations that are previously inaccessible. These representative nanoparticles include dendrimer [ 19 ], clay nanosheet [ 20 ], carbon nanotube [ 18 , 21 ], gold nanoclusters [ 22 ], carbon dot [ 23 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have suggested that the internalization efficiency of nanoparticles was positively correlated with genes being delivered. Most of these particles need to be less than 20 nm in at least one dimension (e.g., quantum dots, [ 68 ] nanoclusters, [ 69 ] carbon nanomaterials, [ 19b,70 ] nanowires, [ 71 ] etc.). In addition, smaller nanomaterials have unique advantages which can achieve suborganelle localization (e.g., chloroplast, [ 19b ] mitochondrion, nucleus, [ 19a ] etc.).…”
Section: Nanomaterial‐mediated Gene‐delivery Systemsmentioning
confidence: 99%
“…[ 16 ] In 2017, clay nanosheets were used to protect double‐stranded RNA (dsRNA) and increase plant virus resistance, [ 17 ] while magnetic nanoparticles realized transgenic plant construction by pollen magnetofection in the same year. [ 18 ] Then, species‐independent, high‐efficient gene‐delivery systems without physicochemical assistance were developed using carbon nanomaterials, [ 19 ] DNA nanostructures, [ 20 ] and gold clusters [ 21 ] in the last three years. Physical (biolistic bombardment, electric pulse), chemical (poly(ethylene glycol) (PEG), not shown), or biological ( Agrobacterium , CRISPR‐Cas) approaches are extensively used in plant cells and whole plants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to widely used nanosensors, nanobiotechnology, especially nanomaterial-assisted biomolecule (such as DNA and RNA) transfer, is a promising research field [ 3 ]. Nanomaterial-assisted biomolecule transfer is involved in transgene expression, genome editing, gene silencing [ 8 , 123 , 124 ]. The physical and chemical properties of the plant cell wall hinder the transformation of biomolecules into plant cells.…”
Section: Nanobiotechnology In Genome Modificationmentioning
confidence: 99%
“…The siRNA delivery platform mediated by CNTs exhibited high silencing efficiency in plant cells, and the NP-based delivery platform showed effective intracellular transferable capacity [ 126 ]. Polyethylenimine-coated Au NPs (PEI-AuNPs) successfully delivered siRNA into intact plant cells, and the target gene expression decreased by at least 76% [ 124 ]. The increasingly popular nanobiotechnology field provides tremendous opportunities for scientists to optimize systems for plant transformation.…”
Section: Nanobiotechnology In Genome Modificationmentioning
confidence: 99%